2008
DOI: 10.2337/db07-1199
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids and Insulin Modulate Myocardial Substrate Metabolism in Humans With Type 1 Diabetes

Abstract: OBJECTIVE-Normal human myocardium switches substrate metabolism preference, adapting to the prevailing plasma substrate levels and hormonal milieu, but in type 1 diabetes, the myocardium relies heavily on fatty acid metabolism for energy. Whether conditions that affect myocardial glucose use and fatty acid utilization, oxidation, and storage in nondiabetic subjects alter them in type 1 diabetes is not well known.RESEARCH DESIGN AND METHODS-To test the hypotheses that in humans with type 1 diabetes, myocardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 47 publications
1
39
0
1
Order By: Relevance
“…8 These human and animal studies have shown that increased oxidative stress correlates with lipid overload, suggesting a role for FA in the generation of ROS, 7,8 whereas an involvement of ROS generated by high glucose concentrations in metabolic abnormalities in diabetic cardiomyopathy remains to be determined. 7 Tumor suppressor, p53, has a well-characterized role in regulating apoptosis and the cell cycle in response to genomic stress; however, its broader roles in organ homeostasis are just beginning to be understood.…”
Section: Clinical Perspective On P 115mentioning
confidence: 99%
See 2 more Smart Citations
“…8 These human and animal studies have shown that increased oxidative stress correlates with lipid overload, suggesting a role for FA in the generation of ROS, 7,8 whereas an involvement of ROS generated by high glucose concentrations in metabolic abnormalities in diabetic cardiomyopathy remains to be determined. 7 Tumor suppressor, p53, has a well-characterized role in regulating apoptosis and the cell cycle in response to genomic stress; however, its broader roles in organ homeostasis are just beginning to be understood.…”
Section: Clinical Perspective On P 115mentioning
confidence: 99%
“…8 These human and animal studies have shown that increased oxidative stress correlates with lipid overload, Received February 9, 2011; accepted October 31, 2011. From the Department of Cardiovascular Medicine, Kyoto Prefectural University School of Medicine, Kawaramachi-Hirokoji, Kamigyo-ku, Kyoto, Japan (H.N., S.M., E.I.-K., M. Kimata, A.H., M. Katamura, Y.O., M.A., Y.M., K.I., M.O., H.M.); the Department of Cardiovascular Medicine, Meiji University of Integrative Medicine, Hiyoshi-cho, Nantan-shi, Kyoto, Japan (E.I.-K.); the Department of Pediatrics, Graduate School of Medicine, Kyoto University, Shogoin Kawahara-cho, Sakyo-ku, Kyoto, Japan (S.S.); and the Department of Pathology and Cell Regulation, Kyoto Prefectural University School of Medicine, Kawaramachi-Hirokoji, Kamigyo-ku, Kyoto, Japan (H.T., T.T.…”
Section: Clinical Perspective On P 115mentioning
confidence: 99%
See 1 more Smart Citation
“…They also demonstrated that the hearts of individuals with type 1 diabetes exhibited increased myocardial oxygen consumption (MVO 2 ) and impaired insulin-mediated glucose uptake. The increase in fatty acid utilization was proportional to serum fatty acid levels, which increased in proportion to the severity of hyperglycemia (Peterson et al, 2008).…”
Section: Rodent Models As a Tool To Study Diabetic Cardiomyopathymentioning
confidence: 99%
“…Rapid intravenous injection of an FFA tracer is useful when aspects of nonoxidative FA metabolism are investigated. Examples include the incorporation of plasma FAs into VLDL-triglyceride (TG) ( 15,16 ) or the storage/uptake of plasma FAs into tissues (17)(18)(19)(20). In addition, intravenous injections can be more convenient than a continuous infusion, because bolus injections obviate the need to keep the volunteers connected to an infusion pump, thus offering greater mobility and freedom during experimental days.…”
mentioning
confidence: 99%